Redesigning pension systems - Marek Góra (IZA World of Labor, 2019)
For decades, pension systems were based on the rising revenue generated by an expanding population (the so-called demographic dividend). As changes in fertility and longevity created new population structures, however, the dividend disappeared, but pension systems failed to adapt. They are kept solvent by increasing redistributions from the shrinking working-age population to retirees. A simple and transparent structure and individualization of pension system participation are the key preconditions for an intergenerationally just old-age security system.
Keywords: H55; I31; J11; J18; 330; pension systems; demographic dividend; transparency of institutions; intergenerational conflict